Low Preoperative Brief Resilience Scale Scores Are Associated With Inferior Preoperative and Short-Term Postoperative Patient Outcomes Following Primary Autograft Anterior Cruciate Ligament Reconstruction - Adam V. Daniel, M.D; Gregory D. Myer, Ph.D., F.A.C.S.M., C.S.C.S.∗D; Troy D. Pashuck, M.D; Patrick A. Smith, M.D (Elsevier, 2024)
Purpose: To assess preoperative Brief Resilience Scale (BRS) scores as they relate to postoperative patient outcomes following primary autograft anterior cruciate ligament reconstruction (ACLR). Methods: All patients who underwent primary autograft ACLR from 2016 to 2021 and had a patient-reported follow-up of 1 year and a clinical follow-up of 6 months were included in final data analysis. Patients completed validated PROMs pre- and postoperatively. All patients were objectively assessed with range of motion (ROM) and KT-1000 arthrometer testing. Return to sport (RTS) data were obtained for all applicable patients. Patients were divided into 3 groups based on ± ½ the standard deviation for the mean preoperative BRS score. Results: In total, 170 patients who underwent primary autograft ACLR with a mean age of 20.1 years (range, 13-57 years) and a mean final follow-up time of 2.9 years (range, 1.0-5.8 years) were included in the final analysis. The mean preoperative BRS scores for the high-resilience (HR, n = 67), average-resilience (AR, n = 42), and low-resilience (LR, n = 61) groups were 28.1 (95% CI, 27.8-28.9), 24.5 (95% CI, 24.3-24.6), and 21.1 (95% CI, 20.5-21.7), respectively (P < .001). The HR group demonstrated significantly higher preoperative and postoperative patient-reported outcome measures (PROMs) compared to the AR and LR groups, with more differences seen with the LR group. The HR group demonstrated better knee extension in postoperative month 3 compared to the LR group (0.6° [95% CI, -1.2° to 0.1°] vs -2.3° [95% CI, -3.3° to -1.3°], P = .006). The HR group demonstrated a faster RTS time compared to the LR group (6.4 months [95% CI, 6.1-6.7] vs 7.6 months [95% CI, 7.1-8.1], P = .002). No differences were seen in RTS rate, knee flexion, or KT-1000 arthrometer measurements between the 3 groups. Conclusions: Low preoperative BRS scores were associated with inferior PROMs preoperatively and in the short-term postoperative period compared to those with higher preoperative BRS scores. Additionally, patients with lower preoperative BRS scores demonstrated a higher degree of knee extension loss 3 months postoperatively as well as a slower RTS. Level of Evidence: Level III, retrospective cohort study.